Effect of Anti-tuberculosis Drugs on Liver Damage Based on Alanine Aminotransferase Level in Pulmonary Tuberculosis Patients - Vera Dianwari; Vycke Yunivita Kusumah Dewi; Nia Kania (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Antituberculosis (anti-TB) drugs could cause serious effect such as hepatotoxicity signed by the increase of Alanine Aminotransferase (ALT) level. Anti-TB drugs are still needed by TB patients who have hepatotoxicity, although clinicians who manage this condition have not recognize whether the advantage of anti-TB drugs is higher than its adverse effect, and there is no data describing about that issue. This study was conducted to discover the liver damage based on the ALT changes before and 12 days after initial anti-TB treatment. Methods: This was a cross-sectional study with total sampling of medical records of pulmonary tuberculosis inpatients from 1st January 2013–31th December 2014 at the Department of Internal Medicine of Dr. Hasan Sadikin.General Hospital. From 141 data, only 14 medical records were eligible to be included in this study. The data used were ALT level before and after therapy. These data were analyzed using Wilcoxon test and considered as significant if p<0.05.Results: The median age of the subject study was 48(18-65) years. Among 14 patients, 8 were female and 6 were male. Five out of fourteen patients developed hepatotoxicity. Four out of five developed grade 1 hepatotoxicity and one out of five developed hepatotoxicity grade 4. The analysis of the data showed the differences of ALT level before anti-TB therapy (22(4-447)) and 12 days after initial therapy (18.5(4-1206)) was not significant (p=0.660).Conclusions: There is no liver damage based on ALT changes after anti-TB treatment so the treatment can be continued.